Preparation method of modified high-toughness polylactic acid
By introducing SSG polymers with dynamic B-O crosslinking structures into polylactic acid, the problem of insufficient brittleness of polylactic acid is solved, and the elongation of break and impact energy absorption is significantly improved without reducing the ultimate tensile strength. Effect.
Patent Information
- Application Number
- CN202411597827.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The inherent brittleness of polylactic acid limits its application in harsh environments. The existing toughening methods often increase toughness with a decrease in strength, making it difficult to take into account both.
By mixing boric acid with hydroxy silicone oil and polymerization, a precursor polymer matrix with a filamentous gloss is prepared, and the oleic acid is fully blended and plasticized to produce an SSG polymer with a dynamic B-O crosslinking structure. The PLA/SSG blend was prepared by melt blending with PLA.
With the extreme tensile strength of polylactic acid almost not lowered, it significantly improves its elongation of break and impact energy absorption, and has wide application prospects.
Smart Images

Figure CN119432029A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymers, and in particular to a method for preparing modified high-strength and tough polylactic acid. Background Art
[0002] Polylactic acid (PLA) is a biodegradable green material made by polymerizing lactide monomers derived from renewable starch. It has good biodegradability and can be completely degraded into CO2 and H2O by microorganisms in nature. However, the inherent brittleness of PLA limits its further industrial application. Faced with increasingly severe service environments, it is urgent to improve the static toughness and dynamic energy absorption performance of PLA. In recent years, researchers have achieved a simple, effective and economical toughening method by melt blending PLA with other polymers at high temperatures, and can customize the final performance of PLA-based composites to a certain extent. For example: Zhang et al. (Materials For Mechanical Engineering 2017, 41, 57-60) melt-blended polybutylene adipate (PBAT) with PLA and found that the addition of PBAT can significantly improve the static tensile toughness of the PLA / PBAT mixture; Dang Haichun (Chemical Industry Progress 2021, 40, 3380-3388) et al.'s research showed that the addition of star-shaped polyurethane (SPUR3) as an additive phase material can improve the dynamic fracture toughness of PLA to a certain extent. However, the improvement in toughness is often accompanied by a decrease in strength. et al. (Journal of Applied PolymerScience 2019, 136, 8-16) successfully prepared a PLA / polyhydroxyalkanoate (PHA) blend, whose elongation at break is nearly 40 times that of pure PLA. Unfortunately, due to the inherent strength of PHA being much lower than that of PLA, the strength and modulus of the final blend are significantly reduced. Similarly, Chinese patents CN113402864A and CN113831711A respectively disclose a specific scheme of using polyamide thermoplastic elastomer and a specific scheme of using polyester elastomer particles to toughen PLA, which also cannot take into account the coordination of strength and toughness. Summary of the invention
[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a modified high-strength and tough polylactic acid, which can significantly improve its elongation at break and impact energy absorption without almost reducing the ultimate tensile strength of polylactic acid, and has broad application prospects in the field of additive manufacturing. In order to achieve the above-mentioned purpose and other advantages according to the present invention, a method for preparing a modified high-strength and tough polylactic acid is provided, comprising:
[0004] S1, mixing boric acid and hydroxy silicone oil and performing polymerization reaction to obtain a precursor polymer matrix with a silky luster;
[0005] S2, mixing the polymer matrix prepared in the above step with oleic acid, and performing sufficient blending and plasticization reaction in a Haake torque rheometer to obtain an SSG polymer having a dynamic BO cross-linking structure;
[0006] S3. Melt-blending the SSG polymer prepared in the above steps with PLA in a double-conical screw, and obtaining a PLA / SSG blend after uniform dispersion, i.e., the high-strength and tough polylactic acid with strain rate hardening energy absorption effect.
[0007] Preferably, the polymerization reaction temperature in step S1 is 200° C., and the mixing ratio of boric acid and hydroxy silicone oil is 80 mg / mL. To ensure sufficient mixing, stirring is required every 20 minutes for more than 2 hours until the reactant develops a filamentous luster.
[0008] Preferably, the mass fraction of the additive oleic acid in step S2 is 1%, and it needs to be fully stirred in the Haake torque rheometer to ensure that the plasticization reaction time is more than 30 minutes.
[0009] Preferably, in step S3, the mass ratio of SSG polymer to PLA is 1:99 to 30:70, the mixing temperature is 200° C., and the melt blending time is not less than 10 min to ensure that SSG is evenly dispersed in the PLA matrix.
[0010] Compared with the prior art, the present invention has the following beneficial effects:
[0011] (1) The PLA / SSG blend of the present invention can significantly improve the elongation at break and impact energy absorption of PLA without almost reducing the ultimate tensile strength, and has broad application prospects;
[0012] (2) The PLA / SSG blend preparation process of the present invention has the advantages of simple operation, easy implementation, industrialization and low cost;
[0013] (3) The PLA / SSG blend of the present invention has excellent processing properties and can be widely used in the fields of additive manufacturing and injection molding. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Fourier infrared spectra of high-strength and tough PLA / SSG copolymer, pure PLA and pure SSG according to the preparation method of modified high-strength and tough polylactic acid of the present invention;
[0015] Figure 2It is a liquid nitrogen brittle fracture morphology of a high-strength and tough PLA / SSG copolymer when the SSG content is 2% according to the preparation method of the modified high-strength and tough polylactic acid of the present invention;
[0016] Figure 3 This is a diagram showing the application of the high-strength and tough PLA / SSG copolymer according to the preparation method of the modified high-strength and tough polylactic acid of the present invention in continuous fiber additive manufacturing. DETAILED DESCRIPTION
[0017] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Description of the raw materials and sources involved in the present invention:
[0019] Boric acid: chemical formula: H3BO3, purchased from Shanghai MacLean Biochemical Co., Ltd.;
[0020] Hydroxy silicone oil: Structural formula: HO[(CH3)2SiO] n H, purchased from Shanghai MacLean Biochemical Co., Ltd.;
[0021] Oleic acid: Chemical formula: C 18 H 34 O2, purchased from Shanghai MacLean Biochemical Co., Ltd.;
[0022] Polylactic acid: Brand: 4032D, purchased from NatureWorks, Inc., USA
[0023] Reference Figure 1 A method for preparing a modified high-strength and tough polylactic acid comprises: preparing a shear-hardening gel polymer (SSG) with a dynamic BO cross-linking structure based on polymerization and plasticization reaction; secondly, melt blending the polymer with a PLA matrix; and finally, preparing a PLA / SSG blend by injection molding. Compared with pure PLA, the PLA / SSG blend disclosed in the present invention has significantly improved elongation at break and impact energy absorption efficiency while almost not reducing the ultimate tensile strength.
[0024] The present invention relates to experimental specification description:
[0025] The tensile properties test specification of high-strength PLA / SSG blends refers to GB / T 1040.2-2022. The specimen type is 1BA and is molded by a micro injection molding machine. During the experiment, the loading rate is 1mm / min and the sampling frequency is set to 20Hz. The specimen state adjustment refers to GB / T 2918-1998, the temperature is 23±2℃, and the relative humidity is 50%±10%. Each specimen test is repeated at least 5 times.
[0026] The impact bending test was used to evaluate the impact energy absorption effect of PLA / SSG blends. The sample size was 80mm×10mm×4mm and was injection molded using a micro injection molding machine. The sample state adjustment was based on GB / T2918-1998, the experimental temperature was 23±2℃, and the relative humidity was 50%±10%. Each sample test was repeated at least 5 times.
[0027] Continuous fiber 3D printing was used to evaluate the processing performance of PLA / SSG blends. The printing nozzle temperature was 200°C, the printing line width was 1.2mm, the layer height was 0.35mm, the experimental environment temperature was 23±2°C, and the relative humidity was 50%±10%.
[0028] The SSG polymer with dynamic BO cross-linking structure used in Examples 1 to 5, i.e., shear hardening glue, was prepared based on the following method:
[0029] Mix 80g of boric acid and 1L of hydroxy silicone oil, and carry out polymerization reaction at normal pressure and high temperature of 200℃ for more than 2h. To ensure sufficient reaction, stir once every 20min, and a reactant A with a large amount of filamentous luster can be obtained.
[0030] Oleic acid was added to the reactant A at a mass fraction of 1%, and the mixture was stirred for more than 30 minutes using a Haake torque rheometer under normal pressure to perform a plasticization reaction, and finally a shear-hardening rubber polymer SSG was obtained. At this time, the reactant SSG will show an obvious strain rate hardening effect, showing a rubber state when slowly loaded, and quickly entering a glassy state when rapidly stretched.
[0031] Example 1
[0032] The polylactic acid particles were dried continuously at 80°C in a blast drying oven for 6 hours to ensure that the water was fully volatilized. Then 9.9g PLA dry particles and 0.1g SSG polymer were weighed, mixed evenly and added to the double conical screw. The mixture was fully melt blended for 8 minutes at a speed of 60rpm and a temperature of 200°C until the torque was balanced and the melt blending was completed to obtain a PLA / SSG blend. Subsequently, the double conical screw outlet was connected to a micro injection molding machine, and the PLA / SSG melt was injected into the mold through an injection molding gun. To ensure smooth demolding, the injection mold temperature was set to 35°C, the injection pressure was 0.5MPa, and the holding time was 30s. After the injection molding was completed, the mold was opened to take out the standard tensile / impact bending test piece.
[0033] Example 2
[0034] The polylactic acid particles were dried continuously at 80°C in a blast drying oven for 6 hours to ensure that the water was fully volatilized. Then 9.8g PLA dry particles and 0.2g SSG polymer were weighed, mixed evenly and added to the double conical screw. The mixture was fully melt blended for 8 minutes at a speed of 60rpm and a temperature of 200°C until the torque was balanced and the melt blending was completed to obtain a PLA / SSG blend. Subsequently, the double conical screw outlet was connected to a micro injection molding machine, and the PLA / SSG melt was injected into the mold through an injection molding gun. To ensure smooth demolding, the injection mold temperature was set to 35°C, the injection pressure was 0.5MPa, and the holding time was 30s. After the injection molding was completed, the mold was opened to take out the standard tensile / impact bending test piece.
[0035] Example 3
[0036] The polylactic acid particles were dried continuously at 80°C in a blast drying oven for 6 hours to ensure that the water was fully volatilized. Then 9.5g PLA dry particles and 0.5g SSG polymer were weighed, mixed evenly and added to the double conical screw. The mixture was fully melt blended for 8 minutes at a speed of 60rpm and a temperature of 200°C until the torque was balanced and the melt blending was completed to obtain a PLA / SSG blend. Subsequently, the double conical screw outlet was connected to a micro injection molding machine, and the PLA / SSG melt was injected into the mold through an injection molding gun. To ensure smooth demolding, the injection mold temperature was set to 35°C, the injection pressure was 0.5MPa, and the holding time was 30s. After the injection molding was completed, the mold was opened to take out the standard tensile / impact bending test piece.
[0037] Example 4
[0038] The polylactic acid particles were dried continuously at 80°C in a blast drying oven for 6 hours to ensure that the water was fully volatilized. Then 9g of PLA dry particles and 1g of SSG polymer were weighed, mixed evenly and added to the double conical screw. The mixture was fully melt blended for 8 minutes at a speed of 60rpm and a temperature of 200°C until the torque was balanced and the melt blending was completed to obtain a PLA / SSG blend. Subsequently, the discharge port of the double conical screw was connected to a micro injection molding machine, and the PLA / SSG melt was injected into the mold through an injection molding gun. To ensure smooth demolding, the injection mold temperature was set to 35°C, the injection pressure was 0.5MPa, and the holding time was 30s. After the injection molding was completed, the mold was opened to take out the standard tensile / notched impact test piece.
[0039] Example 5
[0040] The polylactic acid particles were dried continuously at 80°C in a blast drying oven for 6 hours to ensure that the water was fully volatilized. Then 7g of PLA dry particles and 3g of SSG polymer were weighed, mixed evenly and added to the double conical screw. The mixture was fully melt blended for 8 minutes at a speed of 60rpm and a temperature of 200°C until the torque was balanced and the melt blending was completed to obtain a PLA / SSG blend. Subsequently, the discharge port of the double conical screw was connected to a micro injection molding machine, and the PLA / SSG melt was injected into the mold through an injection molding gun. To ensure smooth demolding, the injection mold temperature was set to 35°C, the injection pressure was 0.5MPa, and the holding time was 30s. After the injection molding was completed, the mold was opened to take out the standard tensile / impact bending test piece.
[0041] Comparative Example 1
[0042] The polylactic acid particles were dried continuously at 80°C in a blast drying oven for 6 hours to ensure that the water was fully volatilized. Then, 10g of PLA dry particles were weighed and added to the double conical screw, and fully melt-blended for 8 minutes at a speed of 60rpm and a temperature of 200°C until the torque was balanced and the melt blending was completed; then, the double conical screw outlet was connected to the micro injection molding machine, and the PLA melt was injected into the mold through the injection molding gun. To ensure smooth demolding, the injection mold temperature was set to 35°C, the injection pressure was 0.5MPa, and the holding time was 30s. After the injection molding was completed, the mold was opened to take out the standard tensile / impact bending test piece.
[0043] The Fourier transform infrared spectra of comparative example 1, examples 2, 5 and shear hardening adhesive are as follows: Figure 1 It can be observed that with the increase of SSG content (0% to 100%), the infrared spectrum at 1753cm -1 The peak intensity of the carbonyl stretching vibration peak (C=O) representing the PLA content shows a trend of decreasing step by step, while the peak at 787 cm -1The methyl symmetric stretching vibration peak (CH3-Si-CH3) representing the SSG content on the left and right showed a gradual increase, which showed that SSG was evenly dispersed in the PLA matrix. Furthermore, by comparing the four absorbance curves, no new absorption peak was observed, which indicated that no chemical reaction occurred between SSG and PLA during the melt blending process.
[0044] The liquid nitrogen brittle fracture section of Example 2 is as follows Figure 2 As shown in the figure, the microstructure of the PLA / SSG blend presents a typical "island structure", in which the circular "islands" represent dispersed SSG submicron particles and the continuous phase is the PLA matrix. This structure reflects the incompatibility between SSG and PLA, verifying that Figure 1 FTIR results in . Therefore, after SSG and PLA were mixed, an emulsion similar to an "oil-water" mixture was formed, and this phase separation microstructure was still maintained after curing. Further measurements showed that when the mixing ratio of SSG / PLA was 98 / 2, the diameter of the dispersed phase (SSG) in the mixture was about 470nm.
[0045] Table 1 Quasi-static tensile and dynamic impact bending test results of Examples 1-5 and Comparative Example 1
[0046]
[0047] It can be observed from Table 1 that when the addition amount of SSG is about 2% (Example 2), the static tensile strength of the PLA / SSG blend reaches the maximum. Compared with the pure PLA in Comparative Example 1, the tensile strength is almost unchanged and the elongation at break increases by nearly 40 times. When the addition amount of SSG is about 10% (Example 4), the dynamic impact energy absorption of the PLA / SSG blend reaches the maximum, with a growth rate of 330%. In addition, the study observed that with the increase of SSG content, the elongation at break and the impact energy absorption of the PLA / SSG blend both showed a trend of increasing and then decreasing. The reason is that on the one hand, when the SSG volume fraction is relatively high, agglomeration is prone to occur, forming a stress concentration area to induce crack sources; on the other hand, the agglomeration phenomenon weakens the deflection energy absorption effect of the interface on the crack, causing the crack to expand directly in the SSG phase and the specimen to break prematurely.
[0048] Figure 3 Some molded products of PLA / SSG blends in continuous fiber 3D printing were displayed. The printing process was smooth and the molding quality was satisfactory, proving that it has excellent processability.
[0049] In summary, the high-strength and tough PLA / SSG blend of the present invention can significantly improve the elongation at break (40 times) and impact energy absorption (330%) of PLA without almost reducing the ultimate tensile strength, and the preparation process is simple to operate, has excellent processing performance and low cost; by designing the addition of shear-hardening glue SSG in different proportions, the tensile strength, elongation at break and impact energy absorption of the blend can be adjusted, and the blend has the ability to be customized.
[0050] The number of devices and processing scales described here are used to simplify the description of the present invention, and the application, modification and variation of the present invention will be obvious to those skilled in the art.
[0051] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing modified high-strength polylactic acid, characterized in that: The following steps are involved: S1, mixing boric acid and hydroxy silicone oil and performing polymerization reaction to obtain a precursor polymer matrix with a silky luster; S2, mixing the polymer matrix prepared in the above step with oleic acid, and performing sufficient blending and plasticization reaction in a Haake torque rheometer to obtain an SSG polymer having a dynamic BO cross-linking structure; S3. Melt-blending the SSG polymer prepared in the above step with PLA in a double conical screw, and obtaining a PLA / SSG blend after uniform dispersion, i.e., the high-strength and tough polylactic acid with strain rate hardening energy absorption effect.
2. The method for preparing a modified high-toughness polylactic acid according to claim 1, characterized in that: The polymerization reaction temperature in step S1 is 200° C., and the mixing ratio of boric acid and hydroxy silicone oil is 80 mg / mL. To ensure sufficient mixing, stirring is required every 20 minutes for more than 2 hours until the reactant has a filamentous luster.
3. The method for preparing a modified high-strength and tough polylactic acid according to claim 2, characterized in that: In step S2, the mass fraction of the additive oleic acid is 1%, and it needs to be fully stirred in the Haake torque rheometer to ensure that the plasticization reaction time is more than 30 minutes.
4. The method for preparing a modified high-toughness polylactic acid according to claim 3, characterized in that: In step S3, the mass ratio of SSG polymer to PLA is 1:99 to 30:70, the mixing temperature is 200° C., and the melt blending time is not less than 10 min to ensure that SSG is evenly dispersed in the PLA matrix.
Citation Information
Patent Citations
Toughened polylactic acid plastic and preparation method thereof
CN113402864A
High-toughness polylactic acid composition and preparation method thereof
CN113831711A
Polylactic acid / shear thickening fluid high-toughness material and preparation method
CN102719065A
Method for toughening polylactic acid based on reversible covalent crosslinking
CN114874397A
Impact-visualized impact protection composite material
CN118703043A